Особливості формування управлінського технологічного центру із професійної майстерності викладачів, як керівників закладів освіти - Силадій Іван; Szilágyi Iván; Маринець Надія; Marinec Nagyija; Nadiia Marynets; Шовш Катерина; Soós Katalin; Shovsh Katerina (Видавництво «Код», 2025)
Резюме. У статті обґрунтовано процес формування професійної майстерності викладачів, як керівників закладами освіти з метою вдосконалення ефективності їх професійної компетентності з управління та можливості створення управлінського технологічного центру сучасного розвитку освітніх технологій в управлінні.

Abstract. The article substantiates the process of forming the professional skills of teachers as heads of educational institutions in order to improve the effectiveness of their professional competence in management and the possibility of creating a management technological center for the modern development of educational technologies in management. Systematicity of educational development management is created by mutual systemic connections: communication and information security, resource and technological support, organizational activities of the subject of management in priority areas, intercultural communication with external influence. Involvement of international projects in educational development management is the main direction of research into real market conditions and educational subsystems. The distribution of spheres of influence of each of the subsystems of management of a certain sphere assumes interaction between them. Autonomy and decentralization in education management are gradually being implemented through state, public institutions of education management. Information, open education management system, which is characteristic of the new model of educational process management due to the combination of state and public support of technological processes. In the ideal model, public organizations are partners of the education management system and provide material and moral assistance to education, constitute a single whole with the education management system. The result of the result in this system directly depends on the level of orientation on priority goals, on the quality of the education management apparatus, the quality of interaction of education system management bodies at different levels of management.
Features of forming a management technological center from the professional skills of teachers as heads of educational institutions
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015978 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-12
Keywords: формування професійної майстерності викладачів; професійна компетентність; керівники закладів освіти